Community Empowerment in Stunting Prevention Through the Complete Stunting Response Mothers Movement (GITa TingTas) - Astuti Setiyani; Hery Sumasto; Agung Suharto (Frontiers in Community Service and Empowerment, 2026)
Currently, Indonesia is facing the problem of stunting, including in Magetan. The prevalence of stunting in 2022 was 17.2%, decreasing by 4.34% to 14.9%. Although this prevalence has decreased, it has not yet reached the 2024 RPJMN target of less than 14%. In Pandeyan Village, 14% of toddlers still experience stunting. Strong efforts are needed to reduce the stunting target. This stunting problem will be more easily prevented through Posyandu (Integrated Health Posts). Posyandu (Integrated Health Post) is an integrated service post for mothers and toddlers in a specific, agreed-upon area, driven by the community to provide health services. Posyandu is a form of community-based health service (UKBM) established by the community based on community initiative and needs, particularly for toddlers. The purpose of this community service is to raise public awareness of stunting prevention through health promotion, education for mothers of toddlers, and the formation of the Complete Stunting Response Mothers Movement Group (GITa TingTas). The method used is training to provide mothers of toddlers with understanding and competencies about exclusive breastfeeding, complementary feeding (MP-ASI), monitoring child growth and development, and the importance of environmental cleanliness. The results of the knowledge test before and after the test (post-test) showed that knowledge about stunting increased from 11% to 23%, and knowledge about stunting increased from 48% to 61%. Meanwhile, in the sufficient and insufficient knowledge categories, the percentages decreased during the pre- and post-tests. The sufficient knowledge category decreased from 23% to 16%, and the insufficient knowledge category decreased from 18% to 0%. Conclusion: The Cadre Training has had an impact on increasing mothers' knowledge about stunting prevention in Pandeyan Village, Maospati District, Magetan Regency. Recommendations: Ongoing training on stunting is needed to ensure mothers remain responsive to stunting prevention. Continuous cross-sectoral and cross-program efforts are needed so that stunting can be addressed with the participation of the entire community.